2014
DOI: 10.5897/ajar2014.8682
|View full text |Cite
|
Sign up to set email alerts
|

Genetic improvement of Gossypium arboreum L. using molecular markers: Status and development needs

Abstract: The genus Gossypium has 45-50 species, of which only four (two allotetraploids and two diploids) enjoy the status of cultivated cotton. Among the four cultivated ones, Gossypium arboreum holds a special place because of the inherent ability to withstand drought, salinity and remarkable resistance to sucking pests and leaf curl virus. However, the species suffer with poor fiber quality traits, low yield and has certain undesirable plant and boll features. Improvement of fiber quality traits of G. arboreum, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 64 publications
(80 reference statements)
0
1
0
Order By: Relevance
“…cultivation features such as early maturity, good abiotic stress tolerance, high fiber resistance, high oil content, high seed index, and excellent plasticity. Several tests have shown that Asian cotton is resilient and displays exceptional tolerance to a variety of pests and diseases, including bollworms (Dhawan et al, 1991), leafhoppers and aphids (Nibouche et al, 2008), rust, fungal (Wheeler et al, 1999) andviral (Mehtre et al, 2004;Akhtar et al, 2010) diseases (Sethi et al, 2014). Before, the introduction of Bt cotton, in different parts of the world, including Gujarat Maharashtra and northern India, the desi cotton was grown on around 27 percent area (Lalitha et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…cultivation features such as early maturity, good abiotic stress tolerance, high fiber resistance, high oil content, high seed index, and excellent plasticity. Several tests have shown that Asian cotton is resilient and displays exceptional tolerance to a variety of pests and diseases, including bollworms (Dhawan et al, 1991), leafhoppers and aphids (Nibouche et al, 2008), rust, fungal (Wheeler et al, 1999) andviral (Mehtre et al, 2004;Akhtar et al, 2010) diseases (Sethi et al, 2014). Before, the introduction of Bt cotton, in different parts of the world, including Gujarat Maharashtra and northern India, the desi cotton was grown on around 27 percent area (Lalitha et al, 2014).…”
Section: Introductionmentioning
confidence: 99%